Surrealist Drawings. (London: Annely Juda Fine Art, 1969)
Bellmer, Hans ; Brauner, Victor ; Castillo, Jorge ; De Chirico, Giorgio ; Dali, Salvador ; Ernst, Max ; Klee, Paul ; Lam, Wifredo ; Magritte, René ; Man Ray ; Moore, Henry ; Paalen, Wolfgang-Robert ; Penrose, Roland ; Picasso, Pablo ; Réquichot, Bernard ; Tanguy, Yves
biografie
Surrealist Drawings, Annely Juda Fine Art, London, May - June 1969
boek